(untitled) (Archives of Criminology, 1984)
Basically, the study concers three problems. Firstly, an attempt was made to explain the mechanism which led to the results obtained by other authors. They found a supposedly most rigorous attitude of the Polish society towards law breakers, which was to become manifest in the demands for relentless and severe punishment of such persons. This highly rigorous attitude has been confirmed in the present study too, yet only in answers to questions drawn up as generally as those put by the mentioned authors. As the level of abstractness of the questions is lowered, the rigorous attitude diminishes, which finds expression, among others, in the disapproval of a number of penalties applied by regulation during the execution of imprisonment. Secondly the attitude of the local community was presented not only towards prisoners, but also towards prison einployees. As compared with many other occupations, the prestige of prison employees is rather low, yet in spite of a certain social isolation, their general opinion is not negative. It is also worthy of attention that the sense of social distance between prisoners and community was les marked than expected. Thirdly, the attitude was described towards prison as a physical object and an institution in the local community. This problem was studies by means of questions about the opinion on the very fact of existence of such an object in twon, the possible impact the prison has on economy, supplies, etc., an the citizens’ feeling of safety. In this formulation, the results fail to point to the existence of markedly negative attitudes, though some socio-demographic features of the examined persons tend to differentiate their answers. The study was realized from 1979 till 1981. In spite of the considerable interval and the differences in the country’s respective social situations, the answers given by the examined persons from both groups were nearly parallel to each other. In 1979, random samples of adults were examined, inhabitants of two towns, about 25 thousand inhabitants each, in which there were prisons. In one of these towns, the prison had been established over 20 years before, while in the second one, it was only a few years old. In each town, 200 persons were examined by means of a questionnaire, which makes the total of 400 examined persons. In 1981, 462 persons were examined by means of the same questionnaire, who were selected with the use of "Quota Sampling" from the population of 10 towns of 11 to 95 thousand of inhabitants, in which there were prisons. The study was intentionally realized in towns of medium population. The aim was to examine communities large enough for the prison not to dominate them on the one hand, and on the other hand, small enough to enable an assumption that a majority of inhabitants have a certain knowledge and opinions about the prison acquired through observation and nin-institutionalized flow of information. As regards the opinion on imprisonment, it should first of all be stressed that over 50 per cent of the examined persons are of opinion that the essential aim oi this type of penalty should be the resocialization of prisoners. About 23 per cent of answers concerning this problem referred to the idea of individual prevention; 12-18 per cent of the examined persons were of opinion that imprisonment should serve to protect the society from the criminal by isolating him for a certain period of time; about 6 per cent of answers pointed to retribution as the aim of punishment, while as few as 2-3 per cent considered the aim to be general prevention. However, to find out if the attitude of the examined persons was rigorous or tolerant, answers to other questions were more significant, that is those concerning the mothods of execution of imprisonment, i.e., the penalties and rewards applied towards prisoners and the rights they enjoy. Here, a significant trend appeared to turn from rigorous to tolerant attitudes as the level of generality of questions lowered. It seems that questions about certain abstract principles, which in the mind of an average man have no connection with any actual situation or person, provoked answers which hinted at a rigorous attitude; yet whenever the same respondent had to answer a question which allowed him to realize the details of a given situation or the position of a given persons in such circumstances, the tolerant attitude prevailed. Thus, for instance, as many as over 70 per cent of the examined persons approved of the most general statement that „in prison, strict discipline should reign”. When another question was asked, this time less generally formulated, if „all amenities of life and attractive activities should be reduced to a minimum”, the numbers of approving and disapproving answers were more or less equal, which points to the lowering of the level of rigorism. The answers to further questions concerning definite cases frankly contradict those given to the former questions and point to a markedly tolerant attitude. Thus, for example, the question if „a prisoner should have free access to newspapers, radio, and TV in his leisure time”, was answered in the affirmative by over 75 per cent of the examined persons. Also the questions about definite penalties and rewards applied towards prisoners were answered in a way which seems to point to the prevalence of tolerant attitudes over rigorism. The majority of the examined persons are for abolition or limitation of penalties provided by prison regulations and for granting the prisoners with a number of rights, such as unlimited receipt of parcels, letters, and visitors from the outside (prison regulations limit the number of such prisoners’ contacts with the outside world and treat any extension of these contacts as a special reward). The examined persons were also for alegal regulation of the sphere of prisoners’ work, pointing to the need for making the working conditions in prison resemble those generally found in State-controlled economy. Also the rational attitude of the public opinion towards prison should be stressed. The prison is perceived as an institution which could play a greater part than before in the life of the local community, particularly through including prisoners in the borader social unit and increasing their participation in the town’s economic activity. The citizens’ expectations point in this direction, accompanied also by the favourable opinion as to the extending of the prisoners’ range of personal liberty outside the prison walls. In this connection, also the attitude of fear of the prisoners was much less marked than had been expected, as well as the bias against them, both of which appear in principle only as regards a small group of dangerous criminals. The attitude of the local community towards prison employees is a completely separate problem. It is characterized by a peculiar ambivalence: on the one hand, prison employees enjoy a good reputation as persons and members of the local community, their financial status perceived as decidedly higher than that of an average citizen. On the other hand, however, the social status of a prison employee is estimated as very low, as compared with other professions, which is accompanied by a stressed disapproval revealed by the examined persons of the very fact of working in a prison. This may lead to a conclusion that in the social consciousness disfavourable opinion persists as to the human relations in prison and the nature of work of prison employees. This is an additional factor which speaks for changes in the system of execution of the penalty of deprivation of liberty which would modernize it and adjust it to the contemporary progressive trends in the world. The present study has not only confirmed the existence of social support for such changes but it has also revealed the conducive atmosphere to a far-reaching reform in this field.